Self-propelled swimming of a flexible plunging foil near a solid wall. (5th July 2016) - Dai, Longzhen; He, Guowei; Zhang, Xing
Abstract: Numerical simulations are conducted to investigate the influences of a solid wall on the self-propelled swimming of a flexible plunging foil. It is found that the presence of a solid wall enhances the cruising speed, with the cost of increasing input power. Rigid foil can achieve high percentage increase in cruising speed when swimming near a solid wall, but the propulsive efficiency may be reduced. Foils with some flexibility can enjoy the enhancements in both cruising speed and propulsive efficiency. Another advantage of the flexible foils in near-wall swimming is that smaller averaged lateral forces are produced. The effects of wall confinement on the wake structure and the vortex dynamics are also studied in this paper. The results obtained in this study shed some light on the unsteady wall effect experienced by aquatic animals and also inform the design of bio-mimetic underwater vehicles which are capable of exploiting the wall effect.